“You’re in my World 1-1 Now!” - The practice of remixing gaming culture on YouTube - Plothe, Theo (AoIR Selected Papers of Internet Research, 2013)
This paper explores content regarding videogame remix culture on YouTube focusing on the comedy channel 2 , a comedy and gaming culture site, whose YouTube channel has nearly 440,000 subscribers and well over 97 million views. 2 videos take a humorous look at video game characters and gaming culture, often making social and meta-commentary by taking characters out of their textual places and remediating them in new, sometimes nuanced or highly controversial contexts. Their remediation of these popular characters often include commentary and narratology from a myriad of extratextual sources in gaming and nerd culture including television, films, comic books, the Internet and popular culture at large. The author investigated the reception of videos within the gaming community on YouTube amongst user-generated comments posted underneath each video. Analysis compiled 150 randomly selected comments from 20 randomly selected videos on 2 ’s YouTube channel, for a total of 3,000 comments. Research questions considered in this paper will include: (1) How do the commenters on 2 remix videos understand these videos as remix?; (2) Are the commenters aware of, or are they concerned with, intertextuality?; (3) What do commenters on 2 videos consider to be important in each video? Emergent categories were coded as an indicator of audience interpretation of the text; derivative, synchronicity, authenticity, comparative, evaluative, communicative, and memetic. The implications of the study suggest gamers interpret the text communally, reifying community norms and culture while inspiring creativity and future remixing.